Exploring Motion Graphics and Humor Concepts for Effective Art and Design Education in Higher Education - Ekwonganan, Roengrit; Disatapundhu, Suppakorn (Rajapark Journal, 2024)
This qualitative research aimed to 1) identify and analyze appropriate motion graphics for instructional media for higher education in art and design courses, and 2) investigate and analyze suitable humor concepts for motion graphics used as instructional media in art and design courses. The research method involved a sample of 187 outstanding motion graphics from the TED-Ed platform in both the Arts and Design categories. Data were collected from three sets of experts using in-depth interviews and the Delphi technique. The research instruments were validated by three experts. The research results were: 1) 59 (out of 187) motion graphics were selected for instructional media in art and design courses, 2) 20 (out of 59) motion graphics with humor were selected, 3) 16 types of the Humor Concept were identified for analyzing motion graphics in this study, 4) The Narrative Theory was identified as the appropriate theoretical framework for analyzing motion graphics, 5) The suitable types of the Humor Concept for motion graphics in higher education were identified such as Bizarre, and 6) the use of the Humor Concept based on the Narrative Theory was identified. These research findings can be effectively applied to motion graphics for instructional media in higher education.